Certain class I HLA alleles and haplotypes implicated in susceptibility play a role in determining specific features of the psoriatic arthritis phenotype. Issue 1 (26th September 2014) - Haroon, Muhammad; Winchester, Robert; Giles, Jon T; Heffernan, Eric; FitzGerald, Oliver
Abstract : Objectives: Psoriatic arthritis (PsA) susceptibility is associated with several different class I alleles, suggesting separate patterns of MHC effect. This exploratory study was based on the hypothesis that heterogeneity of the clinical phenotype of PsA might be explained by differing associations of clinical features with these susceptibility genes. Methods: The clinical phenotype of 282 PsA patients in a cohort previously studied for associations with human leukocyte antigen ( HLA ) -B and HLA-C genotypes was first preliminarily assessed by univariate associations of susceptibility genes with specific clinical characteristics. To explore the potential genotypic effects of pairwise combinations of different HLA-B and C alleles/haplotypes, we created a series of allele/haplotype risk scores combining single alleles/haplotypes separately associated with being in the highest PsA severity propensity tertile based on the features studied by univariate analysis. Results: In exploratory univariate analyses, B*27:05:02 was positively associated with enthesitis, dactylitis and symmetric sacroiliitis, whereas B*08:01:01-C*07:01:01 and its component alleles were positively associated with joint fusion and deformities, asymmetrical sacroiliitis, and dactylitis. HLA-C*06:02:01 was negatively associated with asymmetrical sacroiliitis. The highest propensity score for severe PsA was with B*27:05:02-C*02:02:02, B*08:01:01-C*07:01:01 and B*37:01:01-C*06:02:01, but not the B*27:05:02-C*01:01:01 or B*57:01:01-C*06:02:01 haplotypes . In contrast, B*44 haplotypes were associated with presence of milder disease, and in univariate analysis with a decreased frequency of enthesitis, joint fusion, deformities and dactylitis. Conclusions: Different HLA susceptibility genes were associated with particular features that defined the PsA phenotype of a given patient. Additive interactions between different susceptibility HLA alleles defined the propensity for a more severe or milder musculoskeletal phenotype.